Trilayer Tunnel Selectors for Memristor Memory Cells. Issue 2 (19th November 2015) - Choi, Byung Joon; Zhang, Jiaming; Norris, Kate; Gibson, Gary; Kim, Kyung Min; Jackson, Warren; Zhang, Min‐Xian Max; Li, Zhiyong; Yang, J. Joshua; Williams, R. Stanley
Abstract : An integrated memory cell with a memristor and a trilayer crested barrier selector, showing repeatable nonlinear current–voltage switching loops is presented. The fully atomic‐layer‐deposited TaN1+x /Ta2 O5 /TaN1+x crested barrier selector yields a large nonlinearity (>10 4 ), high endurance (>10 8 ), low variability, and low temperature dependence.